2021
DOI: 10.31579/2768-0487/031
|View full text |Cite
|
Sign up to set email alerts
|

Enterocutaneous fistula; Management Challenges,Areterospective Review of 11 Patients Treated in our Institute

Abstract: Enterocutaneous fistula is a local pathology and systemic disorder. OBJECTIVES: To analyze postoperative outcomes, morbidity, and mortality in patients treated for enterocutaneous fistula in our institute for past 18 months. DESIGN, SETINGS AND PATIENTS: Reterospective review of records of patients presented to Liaquat national university hospital Karachi, Pakistan between Jan 2010 to June 2011 with diagnosis of EC fistula. RESULTS: A total of eleven patients presented with diagnosis of enterocutaneous fist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…A dietician is highly recommended to suggest appropriate treatment based on the patient's nutritional needs. 31 Studies conducted by Gefen et al 32 and Ishaq et al 33 demonstrated that the commencement of feeds prioritizes enteral feeding over total parental nutrition. Other methods of enteral feeding that can be regarded as in managing fistulas include fistuloclysis and relay perfusion (refeeding).…”
Section: Discussionmentioning
confidence: 99%
“…A dietician is highly recommended to suggest appropriate treatment based on the patient's nutritional needs. 31 Studies conducted by Gefen et al 32 and Ishaq et al 33 demonstrated that the commencement of feeds prioritizes enteral feeding over total parental nutrition. Other methods of enteral feeding that can be regarded as in managing fistulas include fistuloclysis and relay perfusion (refeeding).…”
Section: Discussionmentioning
confidence: 99%